The role of hydrogen bonding in the sensitivity of QCM sensors: A spectroscopic study on tosylamido phthalocyanines - Harbeck, Serpil; Atilla, Devrim; Dulger, Ismail; Harbeck, Mika; Gürek, Ayşe Gül; Ozturk, Zafer Ziya; Ahsen, Vefa (Elsevier Science Sa, 2014)
A series of tosylamido substituted phthalocyanines (Pcs) was synthesized, characterized, and studied as sensing material for chemical gas sensors such as the quartz crystal microbalance (QCM). Tosylamido Pcs are appealing molecules for the use as sensitive compounds due to the presence of intramolecular hydrogen bonding of the NH-SO2 groups and the capability of forming intermolecular hydrogen bonds with suitable partners. In this work, the sorption processes and chemical interactions as well as the influence of the intramolecular H-bond on the interaction with organic vapours were studied for the first time using attenuated total reflection (ATR) Fourier transform infrared (FT-IR) spectroscopy. With IR spectroscopy it was possible to clearly identify the active centres of the tosylamido Pcs. The interactions between the Pc molecules and organic vapours as well as the interference effects of water vapour are described. The sorption processes are discussed in detail on the basis of acetonitrile and methanol sorption in dry and humid atmospheres. The results of the spectroscopic and sensor characterization show that the interaction of analyte molecules with the Pcs is strong and selective, when the analyte molecules are able to cleave the intramolecular hydrogen bonding. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Attenuated total reflection (ATR) Fourier transform infrared (FT-IR) spectroscopy; Sorption; Volatile organic compound; Phthalocyanine; Quartz crystal microbalance; Gas sensor